2013
DOI: 10.1021/jz401358w
|View full text |Cite
|
Sign up to set email alerts
|

How to Find Out Whether a 5-Substituted Uracil Could Be a Potential DNA Radiosensitizer

Abstract: Incorporated into genomic DNA, 5-substituted uracils could be employed in human cancer radiotherapy if they could be sensitized to dissociate upon reaction with hydrated electrons. Using the B3LYP/6-31++G(d,p) method, we calculate electron affinities and energy profiles related to the dissociation of the respective anions for a series of uracil derivatives. We demonstrate that for a uracil analogue to be an efficient electron acceptor the uracil substituent has to possess significant electron-withdrawing power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
73
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 34 publications
7
73
0
2
Order By: Relevance
“…9 To harness solvated electrons, which are inactive toward native DNA, 10 2 0 -deoxyuridine derivatives substituted with an electrophilic residue in the C5-position might be used for DNA damage. 11 Beside the necessity of undergoing enzymatic triphosphorylation and incorporation into DNA by enzymatic machinery of a cell, these derivatives should possess high electron affinity and should undergo dissociative electron attachment (DEA) that leads to reactive radicals inside the genome. The two most comprehensively studied examples of such type of 2 0 -deoxyuridines are 5-bromo-2 0 -deoxyuridine (BrdU) and 5-iodo-2 0 -deoxyuridine (IdU).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 To harness solvated electrons, which are inactive toward native DNA, 10 2 0 -deoxyuridine derivatives substituted with an electrophilic residue in the C5-position might be used for DNA damage. 11 Beside the necessity of undergoing enzymatic triphosphorylation and incorporation into DNA by enzymatic machinery of a cell, these derivatives should possess high electron affinity and should undergo dissociative electron attachment (DEA) that leads to reactive radicals inside the genome. The two most comprehensively studied examples of such type of 2 0 -deoxyuridines are 5-bromo-2 0 -deoxyuridine (BrdU) and 5-iodo-2 0 -deoxyuridine (IdU).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the current work we synthesized 5-selenocyanato-2 0 -deoxyuridine (SeCNdU) and determined its susceptibility to be damaged by IR in aqueous solution. We also carried out another radiolytic studies for a modied 2 0 -deoxyuridine derivative that was indicated by our computational model, 11,19 namely for 5-triuoromethanesulfonyl-2 0 -deoxyuridine (OTfdU). The latter compound has been chosen since it is characterized by an exceptionally large thermodynamic stimulus for the DEA process, leading from the OTfdUc À radical anion to the 5-thio-2 0 -deoxyuridine radical.…”
mentioning
confidence: 99%
“…The free energy profiles for the DEA process calculated for only 10 derivatives resulted in two compounds, 5-thiocyanatouracil (SCNU) and 5-oxocyanatouracil (OCNU), which should be comparable or even better radiosensitizers than 5-BrU. 18 …”
Section: Introductionmentioning
confidence: 99%
“…nucleosides with appropriately optimised features. Recently, we have undertaken attempts for rational designing of 5-substituted uracils prone to the dissociative electron attachment (DEA) process [18,19]. As a result, we proposed a series of 5-modified uracils with the DEA characteristics much better than those of BrdU [18,19] and the superior characteristics of some of them were confirmed in the photoelectron spectroscopy [18] and radiolytic studies [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…The first stage of phosphorylation, the conversion of the nucleoside to the nucleoside monophosphate, is usually the rate-limiting step [22]. Hence, the favourable DEA profile [18,19] is necessary, but not a sufficient requirement for an efficient radiosensitising nucleoside. Taking into account that chemical synthesis is frequently not a trivial task and usually is a timeconsuming and costly process, it is difficult to overestimate access to a computational model that could tell, yet before the actual synthesis, if the proposed derivative is a good substrate for nucleoside kinase.…”
Section: Introductionmentioning
confidence: 99%